Integrasi Nilai-Nilai Islam dalam Pengaruh Cuaca di Kelas 3 Sekolah Dasar - Bakil Firnanda Saputra; Sahna Rizki Marpaung; Nur Rahmatia; Rickky Arnold Luzikooij (JURNAL ILMIAH NUSANTARA, 2024)
Weather is a condition of the air or atmosphere in an area that relatively narrow and has a short period of time with parameter components.The main factors are temperature, rainfall, duration of sun exposure, air pressure, speed wind and humidity. Weather is a problem that is still experienced by the community.Especially in weather forecasting. The higher the community's desire to be able.To know the weather conditions in the future accurately, many researchers have arrived now continue to develop research on weather forecasting. Indonesia has four weather conditions, namely hot, cloudy, rainy and sunny weather. It should be remembered that weather changes are not determined by humans but are determined by Allah SWT. Why does this happen? Let's discuss this topic of discussion below.